Victor Klemperer and His Book: The Language of the Third Reich - Oelsner, Miriam Bettina Paulina Bergel (2019)
It is a book of testimonial content published in 1947 in Berlin. It became very well known in the West after the fall of the Berlin Wall. Published in the former GDR did not interest the communist regime. According to Paola Traverso, the Germans came to value the 'LTI' as a way of apologizing to the Jews. Klemperer abandoned his sense of Germanity after suffering all the insults imposed by Nazism.